2016
DOI: 10.1002/rse2.35
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mammalian species richness and occupancy in tropical forest canopies with arboreal camera traps

Abstract: Large and medium-bodied rainforest canopy mammals are typically surveyed using line transects, but these are labour intensive and usually ignore nocturnal species. Camera traps have become the preferred tool for assessing terrestrial mammal communities, but have rarely been used for arboreal species. Here, we compare the efficiency of arboreal camera trapping with line transects for inventorying medium and large-sized arboreal mammals, and assess the viability of using camera traps in trees to model habitat oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 55 publications
4
108
2
4
Order By: Relevance
“…Furthermore, studies have also demonstrated the potential of this tool for recording and studying arboreal and aquatic species, such as marsupials, rodents and primates (Oliveira-Santos et al, 2008;Leuchtenberger et al, 2014;Bowler et al, 2017). As camera traps were set in trails, some species of carnivores were favoured in terms of detection, as crab-eating foxes, ocelots and jaguars (Tobler et al, 2008;Harmsen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have also demonstrated the potential of this tool for recording and studying arboreal and aquatic species, such as marsupials, rodents and primates (Oliveira-Santos et al, 2008;Leuchtenberger et al, 2014;Bowler et al, 2017). As camera traps were set in trails, some species of carnivores were favoured in terms of detection, as crab-eating foxes, ocelots and jaguars (Tobler et al, 2008;Harmsen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we use both arboreal and terrestrial camera traps to directly compare the response of arboreal and terrestrial mammal communities to rainforest disturbance. While the benefits of terrestrial camera traps for understanding community‐level responses have been well documented (Rowcliffe & Carbone, ; Srbek‐Araujo & Chiarello, ; Tobler, Carrillo‐Percastegui, Leite Pitman, Mares, & Powell, ; Tobler, Carrillo‐Percastegui, Zúñiga Hartley, & Powell, ; Tobler, Hartley, Carrillo‐Percastegui, & Powell, ), only recently has arboreal camera trapping become feasible at greater scale; thanks to improvements in battery life, reduced cost and memory capacity (Bowler et al, ; Whitworth et al, ). Consequently, to date there have been no direct comparisons using camera traps to test whether terrestrial and canopy mammal communities respond to rainforest disturbance in a similar way—although previous work has compared arboreal camera trapping with terrestrial transects (e.g., Bowler et al, , Whitworth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While the benefits of terrestrial camera traps for understanding community‐level responses have been well documented (Rowcliffe & Carbone, ; Srbek‐Araujo & Chiarello, ; Tobler, Carrillo‐Percastegui, Leite Pitman, Mares, & Powell, ; Tobler, Carrillo‐Percastegui, Zúñiga Hartley, & Powell, ; Tobler, Hartley, Carrillo‐Percastegui, & Powell, ), only recently has arboreal camera trapping become feasible at greater scale; thanks to improvements in battery life, reduced cost and memory capacity (Bowler et al, ; Whitworth et al, ). Consequently, to date there have been no direct comparisons using camera traps to test whether terrestrial and canopy mammal communities respond to rainforest disturbance in a similar way—although previous work has compared arboreal camera trapping with terrestrial transects (e.g., Bowler et al, , Whitworth et al, ). In this study, we use multispecies occupancy models, which are well suited to analysis of camera data at the community level (Tobler et al, ) and for assessing species‐specific responses to varying levels of forest disturbance (Bowler et al, ; Sollmann et al, ; Tobler et al, ), to answer the question of whether arboreal rainforest mammals show a greater sensitivity to forest habitat degradation compared with their terrestrial counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a photo‐vouchered spatial record of biodiversity, camera traps offer a direct parallel to the museum mammal specimen because the identity of the species can be verified in the photograph, potentially even automatically through artificial intelligence (He et al, ). Although not all species can be visually distinguished (Potter, Brady, & Murphy, ), camera traps are useful for most medium or large terrestrial mammals and have recently proven effective for small mammals and canopy fauna (Bowler, Tobler, Endress, Gilmore, & Anderson, ; McCleery et al, ). Camera traps also have the advantage of clearly recording sampling effort (where they are run and for how long), which is typically not known for museum collections or citizen science observations.…”
Section: Born Digital Biodiversitymentioning
confidence: 99%